Inovação social: Um desafio para o design: O papel do design estratégico no processo de inovação social - Eichenberg, Carolina Hermes (Universidade do Vale do Rio dos Sinos, 2013)
The contemporary system of social organization requires innovative and sustainable solutions that enable society to continue to develop in the best way it can, for a long time, and in equilibrium with the ecosystem. Over the last decades, several actions have been taken to reduce the impact of the human action on the biosphere. However, such initiatives have been sporadic, operating according to reductionist criteria and the current mindset. The theme of social innovation involves a reflection on how to change social relationships so that they modify the individuals’ understanding of the way of handling with things. From this perspective, this research aims at reflecting on the role of strategic design in this process. As this research is related to the design area, the analysis has focused on the concept of systemic discontinuity as proposed by Ezio Manzini (2008). The author has proposed the analysis of radically innovative initiatives carried out in local contexts. In order to do that, the situation of Rede Ideia has been studied. This network consists of solidarity enterprises situated in Porto Alegre-RS. Its objective is to foster social change through the understanding of a solidarity economy. The analysis has been concentrated on two interpretative aspects: the first one has involved case observation; the second has addressed project concepts resulting from a workshop held with students of a specialization course in strategic design. One of the central results of this study is that the role of strategic design in this scenario is to function as both a reference for the understanding of the open system, and an experiment for the conception of complex solutions.
Keywords: Inovação social; Design estratégico; Redes; Soluções habilitantes; Co-design; Strategic design; Networks; Habilitating solutions; Codesign; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial